Exploring the pharmacognostic properties and pharmacological activities of phytocompounds present in Ficus racemosa linn.: A concise review - Nilanjan Pahari; Subhabrota Majumdar; Dipanjan Karati; Rana Mazumder (Elsevier, 2022)
The genus Ficus is a very useful and significant group of trees with various therapeutic properties. Ficus racemosa linn. is a standard-sized tree in the Moraceae family, often known as the cluster fig tree. Ficus racemosa is also known as yajnayoga, udumbara, goolar, dumar, bodda, heibong, jantuphalam, dimri, yogga dumur, and many more names. Ficus racemosa may be found in various countries, including Australia, Malaysia, South-East Asia, Sri Lanka, Pakistan, China, New South Wales, and the Indian subcontinent. It grows naturally near bodies of water but may also be grown artificially. Ficus racemosa is a plant referenced in the old Ayurvedic, Siddha, Unani and Homeopathic traditions with various medicinal activities like as, antidiuretic, antitussive, antiulcer or gastro-protective, anti-oxidant activity, anthelmintic, antibacterial, antipyretic, anticholinesterase, potential anticancer activity, antifilarial, wound healing, antidiarrheal, anti-inflammatory, antiulcer, analgesic, hepatoprotective, radioprotective, fungicidal, hypoglycemic, hypolipidemic, larvicidal, renal anticarcinogenic, cognitive enhancing, and other properties. This Ficus racemosa review included detailed information on its plant description, habitat, microscopical characteristics, and therapeutic usefulness in many activities.